GPRC5A/CXCL8/NLRP3-mediated neutrophil extracellular traps drive gemcitabine-nab-paclitaxel resistance in pancreatic adenocarcinoma - Tianyi Zhu; Qianwen Yang; Xiaozhe Qian; Xiuqi Wu; Jianchen Fang; Yuli Lin; Yukuan Feng; Jian Gao; Qing Xia (Cancer Biology & Medicine)
Objective: Gemcitabine combined with nab-paclitaxel therapy (GnP) represents first-line chemotherapy for advanced pancreatic ductal adenocarcinoma (PDAC). However, the efficacy of GnP is diminished due to chemotherapeutic resistance induced by the tumor microenvironment (TME), the underlying mechanisms of which remain poorly understood. Methods: Clinical data from patients with PDAC who underwent GnP therapy were collected and neutrophil infiltration in tumor tissues was assessed. PDAC cell lines and a mouse model of PDAC were utilized to determine the mechanisms underlying GnP resistance and to focus on tumor-associated neutrophils and neutrophil extracellular traps (NETs). Results: GnP therapy recruited neutrophils to the TME, which resulted in the formation of NETs that contributed to therapeutic resistance in the PDAC murine model. The NET inhibitor, PAD4, enhanced the efficacy of GnP by suppressing tumor growth. Furthermore, GnP significantly upregulated CXCL8 secretion in GnP-resistant MIA PaCa-2 cells, which was mediated by increased expression of GPRC5A in PDAC cells. Screening of classic NET-derived molecules identified cell-free DNA (cfDNA) as a pleiotropic factor that promoted tumor cell proliferation and migration and thereby contributed to chemotherapeutic resistance. In vivo experiments revealed that the combination of GnP with siGPRC5A or DNase was more effective in reducing tumor growth and prolonging survival in PDAC-bearing mice than either treatment alone. Conclusion: The GPRC5A-CXCL8-NET-cfDNA axis has a critical role in the development of therapeutic resistance to GnP in PDAC. Targeting this axis may represent a promising strategy for overcoming GnP resistance and thereby enhancing the efficacy of chemotherapy in PDAC.